Archimedean spiral antenna embedded with frequency selective surface for wideband applications - Mohamud Shire, Abdirahman (2014)
The potential applications such as satellite communication systems, critical military communications, radar warning systems and direction finding systems demand for high gain, uniform unidirectional radiation pattern and wideband antenna ranging from 3.1 GHz to 10.6 GHz. An Archimedean spiral antenna is the most potential candidate in the above mentioned applications as the antenna meets most of the above requirements. However, the practical implementation of spiral antenna is challenged by its bidirectional patterns, relatively low gain and the need for balanced feeding structures. A moveable ground plane is proposed as the backing technique of the spiral antenna by placing it at quarter wavelength behind spiral arms. Despite, the effects of the ground plane on the antenna’s wideband properties, to enable the realization of a conformal antenna without the loss of the antenna’s broadband characteristics, a radian sphere theory is proposed for bandwidth improvement. Microstrip to parallel strip line balun is proposed as the feeding structure of the spiral antenna. This balun has very large bandwidth ranging from 2 GHz to 14 GHz. However, the separation of the ground plane and the spiral arms at quarter wavelength at lower frequencies deteriorate the radiation patterns at middle and higher frequencies. In order to improve the patterns, frequency selective structure is proposed to embed in the cavity of the spiral antenna. The optimized frequency selective surface improves the radiation pattern while maintaining the other parameters such as the gain, bandwidth and axial ratio. All the proposed designs are fabricated and measured. Both simulated and measured results have shown good agreements. Finally, the results show that the proposed Archimedean spiral antenna is the most suitable candidate for above mentioned applications because good circularly polarized unidirectional radiation patterns and high gain of 8 dB to 11.2 dB with bandwidth of more than 140% is obtained.